Formation of Islamic Character of Students Through the Habit of Memorizing Juz Amma at Mimiftahul Huda Banjarejo - Damalia, Arfina Mei; Sangadah, Reni; Purwowidodo, Agus; Huda, Muh. Nurul (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to explore the formation of Islamic character in students through the habit of memorizing Juz Amma at MI Miftahul Huda Banjarejo. Globalization and technological developments have triggered a moral crisis in the younger generation, which can be seen from various negative behaviors such as brawls, use of harsh words, and decreased respect for teachers. Character education based on Islamic teachings is an important solution to protect students from these negative influences. The research method used is a qualitative study with a case study approach, involving observation, interviews, and documentation. The results of the study indicate that the planning of the habit of memorizing Juz Amma at MI Miftahul Huda Banjarejo has been carefully designed through the curriculum, murajaah method, provision of facilities, and support from the principal and teachers. The implementation of this memorization habit has succeeded in instilling Islamic values, such as religiosity, discipline, obedience, perseverance, and love for the Qur'an. Although there are obstacles in the form of memorization difficulties, lack of motivation, and environmental influences, collaborative efforts between teachers, students, and parents are able to minimize these obstacles. Thus, the habit of memorizing Juz Amma is effective in forming the Islamic character of students, which is expected to be a moral and spiritual provision in facing the challenges of the times.